A quantitative understanding on deformation twins generation in single-phase austenitic stainless steels. Issue 6 (13th April 2019) - Shi, Ya; Zhou, Jianqiu
ABSTRACT: Single-phase austenitic stainless steels (316L) have attracted widespread attention from scientists because of their duplex microstructure. In this paper, to have a quantitative understanding on the microstructure deformation of 316L, a physical model based on dislocation theory and strain gradient theory is established to find out the critical conditions when deformation twins generate. The twinning stress and the stress caused by strain gradients are two factors affecting the deformation twinning process. Numerical simulation results reveal that the twinning stress decreases with the increase of twin spacing and the decreases of volume fraction of twins and the orientation of external shear stress; the stress caused by strain gradients increases with the decrease of matrix grain size.